2014
DOI: 10.4253/wjge.v6.i12.571
|View full text |Cite
|
Sign up to set email alerts
|

Quality indicators for colonoscopy: Current insights and caveats

Abstract: Colonoscopy is the diagnostic modality of choice for investigation of symptoms suspected to be related to the colon and for the detection of polyps and colorectal cancer (CRC). Colonoscopy with removal of detected polyps has been shown to reduce the incidence and mortality of subsequent CRC. In many countries, population screening programs for CRC have been initiated, either by selection of patients for colonoscopy with fecal occult blood testing or by offering colonoscopy directly to average-risk individuals.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 118 publications
0
29
0
2
Order By: Relevance
“…Longer withdrawal time can decrease missed lesions . Therefore, withdrawal time of colonoscopy is used as one of the quality indicators in Western countries, although controversial reports exist on this topic . Limited evidence is available about the quality indicators of EGD, which is widely used for gastric cancer screening in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Longer withdrawal time can decrease missed lesions . Therefore, withdrawal time of colonoscopy is used as one of the quality indicators in Western countries, although controversial reports exist on this topic . Limited evidence is available about the quality indicators of EGD, which is widely used for gastric cancer screening in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, guidelines recommend cecal intubation success rates above 90% [52]. Reasons why this goal might not be achieved are female gender, previous abdominal surgery, colitis and diverticulitis or inadequate bowel preparation [3]. Incomplete colonoscopy was identified as an independent risk factor for colorectal cancer [53].…”
Section: Factors Influencing the Adrmentioning
confidence: 99%
“…Although colon cancer screening programs were initiated in the industrialized world, the risk of colon cancer development after a negative colonoscopy - defined as interval carcinomas - remains a problem yet to be addressed [2]. Therefore, improving the adenoma detection rate (ADR) during colonoscopy is the future key tool in preventing colorectal cancer mortality and morbidity [3]. The ADR is defined as the fraction of patients undergoing screening colonoscopy in whom at least one or more adenomas can be detected [4].…”
Section: Introductionmentioning
confidence: 99%
“…Colonoscopy screening and surveillance programmes have a poor effect on mortality from right-sided CRC 2. Adenoma detection rate (ADR) at colonoscopy is inversely associated with the risk of interval CRC; therefore, many endoscopy devices and techniques to maximise right colon ADR have been developed 3. Despite initial studies showing lack of improvement of ADR in the right colon with caecal retroflexion compared with a second look,3 some more recent studies have shown caecal retroflexion to be possible in 90%–96% of patients and increase the number of polyps found up to 13%, leading to a 2% increase in ADR 4 5.…”
Section: Answermentioning
confidence: 99%
“…Although the cancer in this report was identified by CTC, no large studies have shown CTC to be superior to colonoscopy for detecting colorectal polyps. A recent technology showing promising ADR improvement is the full spectrum endoscopy system (a 330° view of the colon lumen from two additional cameras on the scope tip); however, more and larger trials are required 3. In the meantime, it would seem that optimising current practice will provide the best improvement in ADR and with recent evidence, caecal retroflexion at colonoscopy should be considered in patients to reduce CRC incidence.…”
Section: Answermentioning
confidence: 99%